Inhibition of polyisoprenoid and glycoprotein biosynthesis causes abnormal embryonic development. - Carson, D D (1979)
Compactin, a potent inhibitor of polyisoprenoid biosynthesis, induces abnormal gastrulation during sea urchin development at concentrations that have no effect on earlier embryonic development or on macromolecular synthesis. Three lines of evidence suggest that the developmental lesion caused by compactin results from inhibition of dolichol biosynthesis and a concomitant inhibition in the biosynthesis of the oligosaccharide chains of N-linked glycoproteins. (i) Embryos cultured in the presence of compactin gastrulate normally when supplemented with dolichol alone, whereas supplementation with cholesterol or coenzyme Q or both does not prevent the compactin-induced developmental lesion. (ii) Exogenously supplemented [3H]dolichol is incorporated into a compound with the chromatographic properties of oligosaccharide-pyrophosphoryldolichol. (iii) Embryos cultured in the presence of compactin exhibit a decreased capacity to synthesize mannose-labeled glycolipids and N-linked glycoproteins. This decrease in synthesis is abolished if the embryos are cultured in the presence of dolichol along with compactin.